Fatores associados ao abandono do tratamento por usuários do Centro de Atenção Psicossocial Álcool e outras drogas em João Pessoa. - Almeida, Rosilene Alves de (2013)
Adherence to treatment by drug users is an emerging issue, given the high dropout rates reflecting with low levels of successful treatment. To investigate the factors associated with noncompliance with treatment for drug addiction in the city of João Pessoa, in order to provide information to support managers in making decision in the thematic area of attention to drug use. The research used a descriptive exploratory methodological basis of quantitative approach of retrospective character and documentary source to analyze the period at February 2010 to June 2013. The datas were collected at the Center for Psychosocial Alcohol and Other Drugs (CAPSad) and the sample was of 706 records. The analysis was performed in R version 2.15.3 and we used the logistic regression and Pearson chi-square test. Most patients were male, mulatto, single, aged between 21 and 30 years, with low education level, unemployed, good family relationship, who they arrived in the service mainly through spontaneous demand, starting the accompaniment in the semi-intensive modality of treatment. The main drugs of abuse were alcohol, tobacco, marijuana and crack, ranging from 01 to up to 10 the number of drugs used by a single user. Based on the statistical significance of the tests, the results showed as predisposing factors to the treatment dropout the number the drugs of abuse equals 03, single marital status and crack and alcohol consumption. As favorable factors for treatment adherence were the psychiatric hospitalization, bad family relationships, social benefit, and age 41 to 50 years. The health teams must be qualified to deal with the diversity of user drugs, in order to promote health promotion and injury prevention, addressing other forms besides models of conventional treatments, according to the profile of the clientele. In this sense, the work of CAPSad in conjunction with other services is relevant. Given that the logistic regression model wasn't appropriate and on limiting the independence test, alert to the need for a deeper study about the theme.